Roll dynamics and tyre relaxation in heavy combination vehicle models for transient lateral manoeuvres - Santahuhta, Ville (My University, 2019)
Long combination vehicles are the future of road transportation. They have much better energy and transport efficiency compared to traditional transport vehicles. There is a huge interest in using long combination vehicles for transporting goods in Sweden. In Finland, long combination vehicles (34.5 m, 76 ton) were introduced to the roads in the end of January 2019. In Sweden, performance based standards, or PBSs, are becoming an accepted tool for evaluating LCV’s safety and transport efficiency. The goal of this thesis is to produce the simplest possible vehicle models, for the performance based standards that concern lateral dynamics. These models will be used to evaluate those performance based standards, with a minimum number of parameters. The models should include lateral dynamics, roll dynamics due to high load and tyre relaxation. Non-linear tyre model will also be implemented to the simulation models. In simulations, single lane change manoeuvre was used to evaluate the performance of the created vehicle models. The finalized models were validated against high-fidelity models from Volvo GTT. The models were created in Modelica language and implemented to OpenPBS library.
Keywords: Roll dynamics; Tyre relaxation; Vehicle Dynamics; Modelica; Performance based Standards